Dynamics in logistics : First International Conference, Ldic 2007, Bremen, Germany, August 2007 Proceedings - Haasis, Hans-Dietrich; Kreowski, Hans-Joerg; Scholz-Reiter, Bernd (Berlin : Springer, 2008)
28